2000
DOI: 10.3164/jcbn.28.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin C Administration in Alleviation of Organ Damage in Rats Infected with Trypanosoma brucei.

Abstract: SummaryThe effect of vitamin C supplementation on the development of organ pathology in experimental Trypanosoma brucei infection in rats was investigated. Infection caused significant (p<0.05) increases in serum alanine and aspartate aminotransferases as well as in blood urea nitrogen and serum creatinine. Infection also caused significant (p<0.05) hypoproteinemia and hypoalbuminemia as well as decreases in liver and kidney total homogenate proteins. Supplementation of infected rats with vitamin C prevented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
(6 reference statements)
6
6
0
Order By: Relevance
“…Reactive oxygen radicals generated during infections such as trypanosomosis can attack erythrocyte membrane, induce its oxidation and thus trigger haemolysis [23]. The administration of DF was shown in the present study to ameliorate the anaemia induced by the trypanosomes which is in consistent with other findings [3,[26][27][28][29] in rats infected with Trypanosoma brucei brucei and treated with antioxidant vitamins. This study has demonstrated that DF possesses in vivo ability to protect erythrocytes from haemolysis probably due its antioxidant activity; scavenging the ROS produced during the infection thus, causing reduction in the susceptibility of erythrocytes membrane to destruction.…”
Section: Discussionsupporting
confidence: 82%
“…Reactive oxygen radicals generated during infections such as trypanosomosis can attack erythrocyte membrane, induce its oxidation and thus trigger haemolysis [23]. The administration of DF was shown in the present study to ameliorate the anaemia induced by the trypanosomes which is in consistent with other findings [3,[26][27][28][29] in rats infected with Trypanosoma brucei brucei and treated with antioxidant vitamins. This study has demonstrated that DF possesses in vivo ability to protect erythrocytes from haemolysis probably due its antioxidant activity; scavenging the ROS produced during the infection thus, causing reduction in the susceptibility of erythrocytes membrane to destruction.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, severe hypoglycemia has been attributed to be the cause of death in trypanosomiasis (24,25), and parenteral administration of glucose has been shown to delay, but not prevent death, suggesting the involvement of more than one pathogenic process (25). Moreover, mice chronically infected with T. brucei gambiense had significantly increased levels of pyruvate, and lactate, among other metabolites, pointing to an increased glycogen mobilization and increased catabolic activity (26), which is in line with our observations. We noted the depletion of plasma amino acids, including glutamine, leucine, isoleucine, and valine in plasma samples obtained from T. brucei brucei-infected mice.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, there was an associated increase in urinary concentrations of the keto acids, 3-methyl-2-oxovalerate and 2-oxoisovalerate. This association suggested that there was stimulation of ketogenesis in T. brucei brucei-infected mice because ketogenic amino acids are capable of producing keto acids via aminotransferases (26). A decreasing valine to alanine ratio in plasma samples from infected, but not control, animals was noted from day 7 postinfection persisting over the study duration, which concurs with the hypothesis of increased ketogenesis.…”
Section: Discussionsupporting
confidence: 75%
“…It could also be possible that the experimental period was short for reversal of the anemia. Elevation in the levels of serum ALT and AST as well as creatinine and urea concentrations have all been reported in experimental trypanosome infections Umar et al, 2000) partly due to the generation of free radicals and superoxides during trypanosomal infection which causes degenerative changes in vital tissues and organs of infected animals (Umar et al, 2007). The pfks significantly (p50.05) alleviated the disease-induced renal damage in all treatment groups but alleviated the associated hepatic damage in the ITH group only.…”
Section: Discussionmentioning
confidence: 81%